An Alternative Approach for Improving Performance of Organic Photovoltaics by Light-Enhanced Annealing - En-Ping Yao; Chiu-Sheng Ho; Chang Yu; E-Ling Huang; Ying-Nan Lai; Wei-Chou Hsu (International Journal of Photoenergy)
This work proposes an approach for improving the performance of poly(3-hexylthiophene) (P3HT-) based organic photovoltaics (OPVs). P3HT-based bulk heterojunction (BHJ) film can absorb the energy from 532 nm laser light and be transformed into favorable morphology. A combination of traditional thermal annealing and laser annealing improved device performance, with a slight increase in fill factor and a significant improvement in short-circuit current density. Better crystallization and a higher degree of molecular order in the thermal/laser coannealed P3HT-based BHJ film were observed through X-ray diffraction and Raman spectroscopy.